IMPLEMENTASI PELAYANAN ADMINISTRASI KEPENDUDUKAN BERBASIS APLIKASI SISTEM INFORMASI DAN KONEKSITAS DESA (SIKDES) DI KANTOR KEPALA DESA TAMPIRWETAN - Rahayu; Rohmawan Adi Pratama; Yuniva; Islamiyah (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
People as citizens have the right to optimally obtain services from the government, such as administrative services, goods and services. The most basic service organized by the village government is service in the field of population administration, this is because it involves legitimacy as a citizen and is an inherent identity in one's life. In 2017, the Magelang Regency government provided free facilities in the form of an Information System and Village Connectivity application or commonly called SIKDES. The SIKDES application is based on the main data of the Magelang Regency Population and Civil Registry Office which aims to provide accurate and effective population data services because the system is based on information technology. This study aims to examine and determine administrative services through the SIKDES application as well as the obstacles and levels of community satisfaction with administrative services in Tampirwetan Village, Candimulyo District. This research is a qualitative descriptive study with data collection in the form of documentation studies, observations, and interviews. The results showed that the use of the SIKDES application greatly facilitated village officials in serving the community more efficiently. So that it creates community satisfaction, compared to the manual service process.